Additional testing following screening strategies for occult malignancy diagnosis in patients with unprovoked venous thromboembolism. Issue 155 (July 2017) - Robin, Philippe; Le Roux, Pierre-Yves; Le Moigne, Emmanuelle; Planquette, Benjamin; Prévot-Bitot, Nathalie; Roy, Pierre-Marie; Pastre, Jean; Merah, Adel; Couturaud, Francis; Le Gal, Grégoire; Salaun, Pierre-Yves
Abstract: 18 F-Fluorodesoxyglucose Positron-Emission-Tomography combined with Computed-Tomography (FDG PET/CT) might be an attractive tool for cancer screening in patients with venous thromboembolism (VTE), allowing non-invasive whole-body imaging. One of the frequent criticisms to the use of FDG PET/CT for screening is the potential for false positive results leading to unnecessary/invasive investigations. Our aim was to compare the frequency and invasiveness of additional testing following extensive and limited screening strategies for occult malignancy in patients with unprovoked VTE. We analysed patients included in the MVTEP study, a randomized trial that compared a screening strategy based on FDG-PET/CT with a limited screening strategy for occult malignancy diagnosis in patients with unprovoked VTE. All additional diagnostic procedures following screening were recorded and classified as invasive or non-invasive. A total of 394 patients were analysed. Additional diagnostic procedures realized in patients of each group consisted of 59 tests in patients of the FDG PET/CT group versus 53 tests among the patients from the limited screening group (p = 0.65). Overall, 45 (22.8%) patients in the FDG PET/CT group underwent additional diagnostic tests, versus 32 (16.2%) in the limited screening group (absolute risk difference + 6.6%, 95% CI − 1.3 to + 14.4%, p = 0.13). Sixteen (8.1%) patients in the FDG PET/CT group underwent invasive procedures, versus 6 (3%) in the limited screening group (absolute risk difference + 5.1%, 95% CI + 0.5 to + 10.0%, p = 0.03). We found no statistical difference in the number of additional procedures following each screening strategy. However, a higher number of invasive tests were performed in the FDG PET/CT group. Highlights: Venous thromboembolism can occur as the first manifestation of an occult malignancy. Concern for the use of FDG PET/CT for screening is the risk for unnecessary additional tests. No difference of additional procedures following each screening strategy was observed. Higher number of invasive tests in the FDG PET/CT arm.